La falta de regulación en el procedimiento de ínfima cuantía, limita sancionar a los proveedores que no suscriben las órdenes de compra - Quezada Cuenca, Alba Edit (2025)
This research work analyzes the problem of the lack of regulation to sanction suppliers who do not subscribe to purchase orders in the low value procedure. The main objective is to determine how the lack of regulations affects the imposition of the sanction, the obstacles and consequences, as well as to propose improvements in public procurement; for which, the analytical method was applied, integrating qualitative research. The results of the research suggest that the current regulations have regulatory gaps, which affect the right to legal certainty and due process, constituting a legal obstacle to sanction the conduct of suppliers who fail to subscribe purchase orders in the low value procedure. Faced with this legal problem, important consequences are determined, such as deficiencies in the provision of public services, the increase in the cost and time of contracting, the decrease in budget execution, in addition to the affectation of the principle of equality and fair treatment provided for in the LOSNCP. The conclusions reached after carrying out the research work, is that the low value procedure does not have a tool that guarantees the subscription of the order. To this end, it is recommended to establish in the LOSNCP the sanction for a period of one year for the supplier that fails to subscribe the purchase order, for causes attributable to the supplier, the obligation of the RUP, as well as to include in the RLOSNCP the due process for the imposition of the sanction. In this way, legal certainty, publicity, transparency and formal and material equality are guaranteed to the bidders through the contracting procedure and the public interest is safeguarded